Wishes - Van, Muon; Ngai, Victo, 1988- (New York : Orchard Books, an imprint of Scholastic Inc., 2021)
"In this spare, poetic picture book based on author Muon Van's family history and told through a series of wishes, a family packs up everything they own and embarks on a perilous oceanic voyage toward a better life"--
Keywords: Van, Muon -- Juvenile fiction -- Family; Van, Muon -- Fiction; Refugees -- Juvenile fiction -- Vietnam; Immigrants -- Juvenile fiction -- History -- 20th century -- United States; Wishes -- Juvenile fiction; Refugees -- Fiction; Emigration and immigration -- Fiction; Wishes -- Fiction; Picture books